2011
DOI: 10.1007/s11095-011-0584-5
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Metabolism Inhibitors for Cancer Therapy

Abstract: Cancer cells catabolise nutrients in a different way than healthy cells. Healthy cells mainly rely on oxidative phosphorylation, while cancer cells employ aerobic glycolysis. Glucose is the main nutrient catabolised by healthy cells, while cancer cells often depend on catabolism of both glucose and glutamine. A key organelle involved in this altered metabolism is mitochondria. Mitochondria coordinate the catabolism of glucose and glutamine across the cancer cell. Targeting mitochondrial metabolism in cancer ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 183 publications
(189 reference statements)
1
33
0
Order By: Relevance
“…The metformin is widely used for Type Ⅱ diabetes in practical fields and has anti-cancer effects in animal models. Previous studies demonstrated that metformin inhibits complex Ⅰ via the inhibition of ubiquinone reduction and independently stimulates ROS production by the complex Ⅰ flavin [186][187][188] . It might be more clinically meaningful in terms of tolerable safety for a long period as demonstrated in diabetic patients.…”
Section: Therapeutic Implications Of Targeting the Metabolic Interactmentioning
confidence: 99%
“…The metformin is widely used for Type Ⅱ diabetes in practical fields and has anti-cancer effects in animal models. Previous studies demonstrated that metformin inhibits complex Ⅰ via the inhibition of ubiquinone reduction and independently stimulates ROS production by the complex Ⅰ flavin [186][187][188] . It might be more clinically meaningful in terms of tolerable safety for a long period as demonstrated in diabetic patients.…”
Section: Therapeutic Implications Of Targeting the Metabolic Interactmentioning
confidence: 99%
“…Importantly, many tumors show greatly increased glucose uptake and glycolysis, and preferential overexpression of HK-II, whose association with mitochondria via the voltage-dependent anion channel (VDAC, or porin) is essential for the tumor cell metabolic phenotype and also contributes to chemoresistance (Mathupala et al 2009;Mathupala et al 2010;ShoshanBarmatz et al 2010). The vital role of the mitochondrial complex of HK-II, VDAC and the adenine nucleotide transporter (ANT) in particular in tumor cells has also been extensively reviewed (Mathupala et al 2009;ShoshanBarmatz et al 2010;Ramsay et al 2011;Pastorino & Hoek 2003); briefly, this complex regulates life and death by coordinating energy metabolism, metabolite transport between cytosol and mitochondria and also the opening of the mitochondrial permeability transition pore involved in cell death (Mathupala et al 2009;Shoshan-Barmatz et al 2010;Ramsay et al 2011;Pastorino & Hoek 2003). Altogether, glycolysis, HK-II and VDAC are now established as potential therapeutic targets (Mathupala et al 2010;Pelicano et al 2006;Hanahan & Weinberg 2011;Tennant et al 2010;Shoshan-Barmatz et al 2011).…”
Section: Glycolysismentioning
confidence: 99%
“…Such a shift from oxidative phosphorylation to glycolysis for ATP production (the so-called Warburg effect) is one of the hallmarks of carcinogenesis. [2][3][4][5][6] Acidification of cellular environments can lead to cellular toxicity; 7,8 therefore, cells with predominantly glycolytic metabolism influence the state of health of other cells in the surrounding tissue. It remains to be measured how significant such subtle changes might be in a tumor environment, which will require extremely precise measurement of potentially slight metabolic change.…”
Section: Introductionmentioning
confidence: 99%